Determinan Keberlanjutan UMKM Melalui Digitalisasi Marketing, Literasi Keuangan, Inklusi Keuangan, dan Dukungan Pemerintah - Anandita Zulia Putri; Rafika Nur Astuti; Lulu Amalia Nusron (Universitas PGRI Yogyakarta, 2023)
The research aims to examine the effect of digital marketing, financial literacy, financial inclusion, and government support on the sustainability of MSMEs. This study method is quantitative using primary data. Purposive sampling is the sampling technique of choice. The number of samples obtained was 157 MSMEs in the Special Region of Yogyakarta. Analysis of the resulting data using multiple linear regression using the SPSS program. The study results show that digital marketing, financial literacy, financial inclusion, and government support positively affect the sustainability of MSMEs.